PENGEMBANGAN E-BOOK INTERAKTIF BERBASIS APLIKASI BOOK CREATOR PADA MATA PELAJARAN PKK KELAS XI AKUNTANSI - Avanda, Alviona Hewi Briliyant; Pratiwi, Vivi (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This study aims to describe the process of developing an interactive E-book based on the book creator application, analyse the feasibility of interactive E-book s, and students' responses to the use of interactive E-book s developed. This research uses the ADDIE development model which consists of Analysis, Design, Development, Implementation, Evaluation with a website-based interactive E-book output. The instruments used are expert review sheets, expert validation sheets, learner review sheets, and learner response sheets. The results showed that the interactive E-book had been developed in accordance with the ADDIE model. Then the feasibility results show that the validation of the content feasibility component is 87.5% with a very feasible category, the presentation feasibility component is 86.11% with a very feasible category, the language feasibility component is 94% with a very feasible category and the feasibility component is 91.67% with a very feasible category. While the response of students at SMK Negeri 4 Surabaya was 98.32% with a very good category. According to the results of the validation of experts and the response of students, it shows that the interactive E-book produced can be well received for learning activities.